Influence of different local anesthetics on atracurium neuromuscular blockade on rats - Trizotti,João Paulo Soares da Silva (2020)
Abstract Introduction: The association between local anesthetics (LA) and neuromuscular blocking (NMB) drugs in clinical practice, and the possibility of interaction between these drugs has been investigated. LAs act on neuromuscular transmission in a dose-dependent manner and may potentiate the effects of NMB drugs. Objective: The aim of this study was to evaluate, in an experimental model, the effect of lidocaine and racemic bupivacaine on neuromuscular transmission and the influence on neuromuscular blockade produced by atracurium. Methods: Male Wistar rats, weighing from 250 to 300 g were used. The preparation was set up based on a technique proposed by Bülbring. Groups were formed (n = 5) according to the drug studied: lidocaine 20 µg.mL−1 (Group I); racemic bupivacaine 5 µg.mL−1 (Group II); atracurium 20 µg.mL−1 (Group III); atracurium 20 µg.mL−1 in a preparation previously exposed to lidocaine 20 µg.mL−1 and racemic bupivacaine 5 µg.mL−1, Groups IV and V, respectively. The following parameters were assessed: 1) Amplitude of hemi diaphragmatic response to indirect stimulation before and 60 minutes after addition of the drugs; 2) Membrane potentials (MP) and miniature endplate potentials (MEPPs). Results: Lidocaine and racemic bupivacaine alone did not alter the amplitude of muscle response. With previous use of lidocaine and racemic bupivacaine, the neuromuscular blockade (%) induced by atracurium was 86.66 ± 12.48 and 100, respectively, with a significant difference (p = 0.003), in comparison to the blockade produced by atracurium alone (55.7 ± 11.22). These drugs did not alter membrane potential. Lidocaine initially increased the frequency of MEPPs, followed by blockade. With the use of bupivacaine, the blockade was progressive. Conclusions: Lidocaine and racemic bupivacaine had a presynaptic effect expressed by alterations in MEPPs, which may explain the interaction and potentiation of NMB produced by atracurium.